THE RELATIONSHIP OF LACTOFERRIN GENE WITH MILK PRODUCTION AND ITS COMPONENT IN HOLSTEIN COW - & Shaker, Alkudsi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This resesrch was conducted at the Dairy Cattle Farm pertaining to the Department of Animal Production, College of Agriculture in Abu-Ghraib (20 km West of Baghdad) and Al-Jaderiah, as well as at the Biotechnology  Physiology Laboratory at the College of Agriculture, University of Baghdad , Al-Jaderiah, and in collaboration with the Laboratory that specific for molecular genetic analysis during the period from 27/11/2015 to 1/04/2016. The objective of this study was to identify the polymorphism of  lactoferrin gene and their relationship with some growth and productive traits for 28 Holstein cows and their borns, along with the study of some immunological indicators. The distribution percentages of lactoferrin gene polymorphism in cow's sample were 17.86 and 82.14 % for AA and AB respectively. The variation between these percentages were highly significant (P≤0.01). The allele frequency for A and B were 0.59 and 0.41 respectively, according to the lactoferrin gene analysis carried out currently.  The effect of lactoferrin gene polymorphism on milk yield was highly significant (P≤0.01), being cows with AB yielded 2447.37 ± 209.06 kg, while those with AA yielded 1205.70 ± 120.14 kg. The lactation period has not significantly affected by lactoferrin gene polymorphism. The influence of lactoferrin gene polymorphism was obvious on milk fat (P≤0.01) and ash (P≤0.05) percentages, while other milk components (lactose, protein and solid non-fat) did not. It can be concluded from the study of gene expression for lactoferrin gene, the possibility of adopted them in cattle breeding strategy,. We also recommend to apply the study on a larger sample and for several productive lactions that will give more accurate results from the application of culling and replacement strategies.